Analysis of the Effectiveness of Mudharabah and Musyarakah Financing Models in Islamic Financial Institutions - Fatur Rahman Karim (Journal of Islamic Economy, 2024)
This study aims to analyze the effectiveness of the mudharabah and musyarakah financing models in Islamic financial institutions. The method used is the Systematic Literature Review (SLR), which allows researchers to evaluate and synthesize various relevant studies in order to obtain more comprehensive conclusions on the topic. SLR is conducted by collecting articles that discuss mudharabah and musyarakah financing and analyzing the factors that influence the effectiveness of both models. Literature searches are conducted through academic databases such as Google Scholar, Scopus, and JSTOR, with selected articles filtered based on predetermined inclusion and exclusion criteria. Relevant articles were published in the last five years and focused on Islamic financing. Researchers conducted a thematic analysis of selected articles to identify emerging themes related to the effectiveness of these two financing models. The results of the study indicate that the mudharabah and musyarakah models are effective as alternative financing for the MSME sector, allowing business actors to obtain capital without being trapped in interest obligations. However, the effectiveness of this model is highly dependent on good risk management, clarity of profit and loss sharing, and transparency and trust between Islamic financial institutions and customers. Therefore, Islamic financial institutions need to improve their supervision and risk management systems to ensure the successful implementation of this financing model.